The Relationship between Wrist Flexibility and Hand-Eye Coordination on Table Tennis Backhand Drive Shot Results in Disabled Table Tennis Athletes at NPC Club - Permadi, Andes; Prabowo, Andika; Raibowo, Septian; Rizky, Oddie Barnanda; Ilahi, Bogy Restu (Universitas Negeri Surabaya, 2024)
Purpose: This study aims to determine the relationship between wrist flexibility and hand-eye coordination on the results of backhand drive shots. Materials and Methods: This research includes quantitative research with a correlation approach. The population of this study was 20 table tennis athletes of the Lubuklinggau City NPC Club. To determine the sample, purposive sampling was used, namely active athletes as many as 16 athletes. The data analysis used is the correlation test. Result: Based on the results of data analysis, wrist flexibility has a relationship to the results of backhand drive shots with a correlation value (r) = 0.661, a significant relationship and a strong level of relationship. Hand-eye coordination is a relationship to the results of the backhand drive with a correlation value (r) = 0.591, a significant relationship and a moderate level of relationship. The results of the multiple correlation test between wrist flexibility and hand-eye coordination, based on the results of the backhand drive correlation value (r) = 0.506, show a significant relationship with a moderate level of relationship. Conclusion: There is a significant relationship between Wrist Flexibility and Hand-Eye Coordination in Table Tennis Backhand Drive Stroke Results.